An essential ubiquitin-conjugating enzyme with tissue and developmental specificity in th nematode Caenorhabditis elegans. - Zhen, M (1996)
The ubc-2 gene in Caenorhabditis elegans encodes a ubiquitin-conjugating enzyme (E2) homologous to yeast UBC4 and UBC5. UBC4 and UBC5 are individually dispensable class I E2 enzymes involved in the degradation of short-lived and abnormal proteins. Transgenic analysis using ubc-2-lacZ fusions and in situ immunofluorescence indicate that ubc-2 is abundantly expressed in most tissues of embryos and early larvae, but becomes specific to the nervous system in L4 larvae and adults. This suggests that the functions of this type of E2 are developmentally regulated in C.elegans. This hypothesis is supported by antisense analysis, which shows that blocking the expression of ubc-2 has a more severe effect in early developmental stages than in later stages. Through complementation of previously identified essential genes in the vicinity of ubc-2, we demonstrate that ubc-2 corresponds to let-70, a gene essential for C.elegans larval development. One let-70(ubc-2) allele contains a His75-->Tyr substitution, while another has an altered splice donor site.